131k views
2 votes
Which expression is equivalent to (2-3x) (2+3x) ?

1 Answer

2 votes

Answer:


4-9x^(2)

Explanation:

in the first parenthesis, multiply the FIRST number (2 - 3x) by the numbers in the OTHER parenthesis. (2 + 3x)


(2-3x)(2+3x)

it would look like:


2(2) = 4\\2(3x) = 6x

Next, multiply the SECOND number (2 - 3x) by the numbers in the OTHER parenthesis. (2 + 3x)


-3x(2) = -6x\\-3x(3x) = 9x^2

Now, add like terms. Your answer should either be:


4+6x-6x+9^2 OR
4 -9x^2

User Fernando Redondo
by
5.4k points